The Werther Effect revisited: Measuring the effect of news items on user behavior - Yom-Tov, Elad; Fischer, Shira H.; Yom-Tov, Elad (7th Temporal Web Analytics Workshop (TempWeb 2017), 2017)
People are moved to act following exposure to media coverage of speciﬁc events. For example, the “Werther Eﬀect” is the popular term for the observed increase in suicides following media coverage of suicides. Here we develop a ﬁne grained method for assessing the eﬀect of news stories on the intentions of internet users. Our method assesses the likelihood that a person was exposed to a given news story via the temporal and spatial distances between the location of the person and the location of the news story and/or the website where it was published. This analysis of likelihoods allows us to estimate the contribution of a particular news story to a person’s intent, as manifested in speciﬁc, intent driven, search engine queries. Data were gathered over a ten-month period and cover both the search engine queries of a large population and the news stories to which this population was exposed. We estimated the contribution of news stories to negative eﬀects (i.e. media coverage of suicides and their eﬀect on queries indicating suicidal intention), and positive eﬀects (e.g. media coverage of disease prompting queries into disease screening). We demonstrate that the contribution of news stories can be assessed at the level of individual users, and we analyzed titles and phrases therein for their eﬀect. Finally, we propose a predictive model to be utilized by media outlets to predict the likely eﬀect of speciﬁc stories prior to their publication.